Assessing the transition between school and university: Differences in assessment between A level and university in English. (April 2017) - Wilson, Frances; Child, Simon; Suto, Irenka
High stakes assessments are commonly used at the end of secondary school to select students for higher education. However, growing concerns about the preparedness of new undergraduates for university study have led to an increased focus on the form of assessments used at upper secondary level. This study compared the structure and format of assessments used at upper secondary level (GCE A level qualifications), and the first year of undergraduate study of English literature in England. Greater diversity of assessment was found at university compared to A level, while there was little difference in the level of scaffolding and guidance provided in assessment materials. We conclude that it seems inevitable that some students will meet forms of assessment with which they are unfamiliar at university. Implications for the design of first-year undergraduate courses are discussed.